Radar measured rain attenuation with proposed Z-R relationship at a tropical location - Yeo, Jun Xiang (2015)
Attenuation measurements from two Ku- and a Ka-band satellite beacon signals in a tropical site, Singapore are presented. A new Z–R relationship (Z = 61.75 · R1.61) is derived using rainfall rate data from rain gauge. Rainfall rates predicted from Radar data using the proposed relationship and the Singapore data set are used to compute the earth–satellite path rain attenuation. The measured attenuations from satellite beacon receivers match well with that computed values using the Radar data.